Дослідження підходів до діагностики та обслуговування автомобілів на альтернативних джерелах енергії - Муден, Камал (Харківський національний автомобільно-дорожній університет, 2024)
The object of this research is the diagnosis and maintenance processes of cars powered by alternative energy sources. The purpose of this research is to study and compare the approaches to the diagnosis and maintenance of cars operating on alternative energy sources. Methods of the Research - literature review, analytical research methods and statistical data processing. Practical significance of the research. By developing and refining diagnostic and maintenance procedures, the research will contribute to improving the reliability and safety of vehicles powered by alternative energy sources. This is crucial for gaining consumer trust and increasing the adoption of these technologies.
Keywords: TRANSPORT; ELECTRIC VEHICLE; CHARGING INFRASTRUCTURE; HYDROGEN; BATTERY; POWER MANAGEMENT; FUEL CELL ELECTRIC VEHICLES; BIOFUEL VEHICLES; HYBRID ELECTRIC VEHICLES